AN ANALYSIS OF VIOLATION OF MAXIMS BY MAIN CHARACTERS IN THE AGE OF ADALINE MOVIE - Wulandari, Fevi; Arifin, M. Bahri; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This thesis discussed two problems: analyzing the maxims violated by the main characters in The Age of Adaline movie and the reasons why the main characters violated the maxims in the movie. The researcher chose two main characters who were influential in building the story. This is research was conducted using a qualitative method of content analysis because it focused on understanding the phenomenon of language in depth. In this study, data collection was done by watching and reading dialogues in The Age of Adaline movie This result of this study showed that they were nineteen dialogues containing all types of maxims violated by main characters. In this study, the main characters violated the quantity of maxim more often in conversation because it provides more information than needed. The reasons for violating the maxims were saving face, protecting the answer, avoiding the discussion, pleasing the interlocutors, communicating self-interest and misleading counterparts. It was also revealed that the main characters most frequently violated the maxim to avoid discussion due to their dislike about certain topics such as identity and work which causes misunderstandings between the main characters. The reason the main character often uses was avoiding the discussion because in The Age of Adaline, the main character tried to avoid her true identity to avoid things that will make her identity known to everyone.